Green Blue Infrastructure methodologies and design proposals - Acierno, Antonio; Coppola, Emanuela (TRIA Urban Studies, 2022)
The Green Blue Infrastructure is a multifunctional and flexible approach based on various layers, composing an organic network. This design methodology has the potential to recompose together fragments of the contemporary city, generating positive effects on both communities and landscape while improving the health and well-being of people and ecosystems. In this book, different project proposals are presented, facing many contexts and themes, all of which can be traced back to the theory of Green Blue Infrastructure. In the first part of the volume, the attention is focused on the Italian territory, in particular in the South, where the design of Green Blue Infrastructures is still very limited: the presented projects address some relevant issues of this ecological approach, like health issues, multifunctionality, connectivity in the green-grey continuum and resilience, proposing design tools and project elements but also possible improvements in the governance and in the management. In the second part of this book, it is possible to recognise two main methodological approaches to the Green Blue Infrastructure. The first one deals with multi-scalarity of ecological design in the context of European coastal landscapes; the second one considers the relationship between the continuity of green networks and the safety and liveability of public spaces. Anyway, both methodologies try to cope with different aspects of the socio-environmental development, following the principle of integration between urban safety, regeneration and Green Blue Infrastructure design.